Analisis Pemilihan Supplier Timah Menggunakan Metode AHP dan TOPSIS di IKM Geulis Automotif - Nugraha, Dimas; Ulum, Rikzan Bachrul; Wibowo, Priyo Ari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Supplier selection is a crucial aspect in supporting smooth production processes, particularly in ensuring the availability of high-quality raw materials. This study aims to develop a decision support system to determine the best tin Supplier using the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). AHP is applied to determine the weights of five main criteria: price, quality, availability, delivery, and service, with delivery receiving the highest weight of 0.484. Subsequently, TOPSIS is used to rank Supplier alternatives based on the calculated weights. The results show that Supplier 2 is the best choice according to AHP with a preference value of 0.333, while TOPSIS recommends Supplier 1 with a preference value of 0.604. This difference reflects the distinct evaluation approaches of each method. Combining AHP and TOPSIS offers a more objective and comprehensive assessment for more accurate Supplier selection decisions.